2021
DOI: 10.1063/5.0047807
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dominance of the gradient drift or Kelvin–Helmholtz instability in sheared ionospheric E × B flows

Abstract: Studies have shown that in sheared E×B flows in an inhomogeneous ionospheric plasma, the gradient drift (GDI) or the Kelvin–Helmholtz (KHI) instability may grow. This work examines the conditions that cause one of these instabilities to dominate over the other using a novel model to study localized ionospheric instabilities. The effect of collisions with neutral particles plays an important role in the instability development. It is found that the KHI is dominant in low collisionality regimes, the GDI is domin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The plasma loss creates the density trough, and the steep density gradient can be a source of the plasma instability. For weaker and latitudinally broader SAPS flows, the trough density gradient has been shown to create density irregularities through the gradient drift instability and Kelvin−Helmholtz instability (Rathod et al, 2021). Steeper density and velocity gradients for intense SAID may create an even stronger instability.…”
Section: Chemistry and Emission Mechanismsmentioning
confidence: 99%
“…The plasma loss creates the density trough, and the steep density gradient can be a source of the plasma instability. For weaker and latitudinally broader SAPS flows, the trough density gradient has been shown to create density irregularities through the gradient drift instability and Kelvin−Helmholtz instability (Rathod et al, 2021). Steeper density and velocity gradients for intense SAID may create an even stronger instability.…”
Section: Chemistry and Emission Mechanismsmentioning
confidence: 99%
“…The behavior of this phenomenon is typical of two-dimensional turbulence [82], especially for the Kelvin-Helmholtz type fluid instability [83]. In this context, the origin of the instability may be associated with drift velocity differences across the cathode plasma.…”
Section: Plasma Oscillationsmentioning
confidence: 97%
“…Therefore, the charge exchange between the ions and neutrals will generate a drag force that decreases the strength of the sheared E × B flow. Previous studies (Keskinen et al 1988;Khomenko 2016;Rathod et al 2021) have reported that the electrostatic KHI can be damped by collisions and that ion-neutral interactions can lead to a modification of the onset criteria and the growth rates of KHI and Rayleigh-Taylor instability (RTI) encountered in chromospheric heating solar plasmas. Thus, the effect of ionneutral collisions on the sheared E × B flow and the accompanying plasma instabilities in the ion cyclotron frequency range has been investigated in order to interpret the dynamical processes in partially ionized plasma such as the solar chromosphere and planetary ionosphere in this work.…”
Section: Introductionmentioning
confidence: 99%